Role of Second Transplantation for Children With Acute Myeloid Leukemia Following Posttransplantation Relapse. Issue 4 (16th December 2015) - Taga, Takashi; Murakami, Yoshitaka; Tabuchi, Ken; Adachi, Souichi; Tomizawa, Daisuke; Kojima, Yasuko; Kato, Koji; Koike, Kazutoshi; Koh, Katsuyoshi; Kajiwara, Ryosuke; Hamamoto, Kazuko; Yabe, Hiromasa; et al.
Abstract : Background: In children with acute myeloid leukemia (AML), hematopoietic stem cell transplantation (HSCT) in first remission is indicated for patients with a relatively high risk of relapse. Second HSCT is a curative option; however, few reports have been published about a second HSCT in children for AML with posttransplantation relapse. Procedure: Using the database provided by the Japanese Society of Hematopoietic Cell Transplantation, we analyzed 46 children with AML who underwent a second allogeneic HSCT after achieving a second remission. Results: The median duration from the first to second HSCT was 20 months, and the source of the second HSCT was related bone marrow (BM) in 22, related peripheral blood in 6, unrelated BM in 14, and unrelated cord blood in 4 patients. Twenty‐five children eventually died of the following causes: progressive disease in 14 and transplant‐related toxicities in 9. The 5‐year overall survival rate was 41.7 ± 7.7%. An interval of less than 24 months between the first and second HSCT was a significant poor prognostic factor. Conclusions: Children with AML who experience a relapse after HSCT in first remission have a good chance of survival with a second HSCT if a second remission is achieved.